2009
DOI: 10.1136/jramc-155-03-02
|View full text |Cite
|
Sign up to set email alerts
|

Penetrating Cardiac Injury

Abstract: It is understood that penetrating cardiac trauma is a highly lethal injury and those surviving to hospital have an overall mortality approaching 80%. Reported mortality figures vary widely and are extremely dependent on mechanism of wounding, cardiac chambers involved and possibly the presence of cardiac tamponade. Despite significant advances in prehospital care, operative techniques, and intensive care management, the mortality has not changed over several decades. This article will review the anatomic regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0
17

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 42 publications
1
58
0
17
Order By: Relevance
“…Bu esnada mayi replasmanı ile hemodinamik stabilite hızla sağlanarak defektin nasıl kapatılacağı planlanır. [15] Basit miyokard laserasyonları pledget destekli polipropilen dikişler ile miyokarddan tam kat geçilerek onarılabilir. Koroner damarlara yakın bölgedeki laserasyonlarda, matress sütürler damarın altındaki miyokard dokusundan, kan akımını engellemeyecek şekilde geçilmelidir.…”
Section: Discussionunclassified
“…Bu esnada mayi replasmanı ile hemodinamik stabilite hızla sağlanarak defektin nasıl kapatılacağı planlanır. [15] Basit miyokard laserasyonları pledget destekli polipropilen dikişler ile miyokarddan tam kat geçilerek onarılabilir. Koroner damarlara yakın bölgedeki laserasyonlarda, matress sütürler damarın altındaki miyokard dokusundan, kan akımını engellemeyecek şekilde geçilmelidir.…”
Section: Discussionunclassified
“…Available data in the literature regarding the survival benefit from tamponade after cardiac surgeries remains contradictory. While increased survival from tamponade has been reported in a number of studies, some reports have shown the absence of such a benefit (1,16,19). Moreover, the cardiovascular condition and consciousness status of victims upon hospital arrival significantly contribute to the predictable outcome of penetrating cardiac injuries (13).…”
Section: Discussionmentioning
confidence: 99%
“…Penetrating cardiac injuries are among the most lethal of all traumatic injuries, with many studies reporting mortality rates of 70-90% (1)(2)(3). The number of such injuries is a very small proportion of annual trauma admissions (0.1%) in most reports (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Ancak bunlar miyokardda daha çok hasara neden olabilir. Basit dijital kompresyon ile geçici olarak kanama durdurmak basit ve etkili bir yöntemdir (35). Atriyum yaralanmalarında vasküler klamp uygulanarak, 3/0 ya da 4/0 polipropilen sütürlerle onarım yapılabilir.…”
Section: Penetran Kalp Yaralanmalarıunclassified
“…Kalp kaldırıldığında hipotansiyon, bradikardi ve arrest ortaya çı-kabilir. Bu tür onarımlarda, kalbin tolere ettiği ölçüde kısa aralıklarla kalp kaldırılıp tekrar hemodinami toparlayana dek bekleyerek, her seferinde hasarın yerinin tesbiti, sütürlerin geçilmesi ve bağlanması yavaş yavaş yapılarak onarım gerçekleştirilebilir (35). Bu durumlarda, kalp hızını yavaşlatıp kısa süreli asistoli sağlaması için adenosine infüzyonu uygulanabilmektedir (36).…”
Section: Penetran Kalp Yaralanmalarıunclassified